An integrated parenting intervention for maternal depression and child development in a low‐resource setting: Cluster randomized controlled trial. Issue 9 (19th May 2021) - Husain, Nusrat; Kiran, Tayyeba; Fatima, Batool; Chaudhry, Imran B.; Husain, Mina; Shah, Sadia; Bassett, Paul; Cohen, Nancy; Jafri, Farhat; Naeem, Shehla; Zadeh, Zainab; Roberts, Chris; et al.
Abstract: Background: Rates of depression among Pakistani mothers are high, leading to poor developmental outcomes in their children. This study tested the effectiveness of a manualized integrated parenting program; Learning through Play Plus (LTP+) for maternal depression in Karachi, Pakistan. Methods: A cluster randomized control trial conducted from January 2014 to December 2015 across 120 villages in Karachi. A total of 774 depressed mothers aged 18–44 years with children aged 0–30 months old, were included. Villages were randomized to receive LTP+ added to treatment as usual (TAU) or TAU alone. Primary outcomes were severity of maternal depression at 3 and 6 months measured by the Edinburgh Postnatal Depression Scale and child socio‐emotional development at 6 months measured by the Ages and Stages Questionnaire (ASQ). Secondary outcomes included maternal anxiety, quality of life, social support, parenting competence, and knowledge about child development. Results: Mothers in the LTP+ group reported significantly lower depression scores compared to those in the TAU group (6.6 vs. 13.8, effect size [ES]: −7.2; 95% confidence interval [CI]: −8.2, −6.1) at 3 and 6 months (7.2 vs. 12.00; ES: −4.6; 95% CI: −5.9, −3.4). Child socio‐emotional development at 6 months was significantly better in the LTP+ group on all domains of the ASQ. There were also statistically significant improvements on all secondary outcomes at 3‐ and 6‐month follow‐up. Conclusion: In low‐resource settings like Pakistan, low‐cost integrated parenting interventions delivered by lay health workers can provide effective treatment for depressed mothers, leading to improvements in child development.